Capacity WORKS - GIZ (2014)
One of GIZ’s core competencies is understanding how cooperation works in societies, and supporting that process. The kind of process we mean is cooperation between state, civil society and private-sector actors who wish to jointly shape societal changes. GIZ has systematised its knowledge on how to achieve this, and made it available in the Capacit y WORKS management model. The model describes how to manage cooperatio n systems.